Analisis Pendukung Keputusan Menggunakan Metode TOPSIS Untuk Pemilihan Tender Firewall DKI Jakarta - Pratomo, Antoni Roozaq (Jurnal Pengembangan Rekayasa dan Teknologi, 2022)
Firewall is a system or device that allows traffic that is considered safe to traverse and prevent insecure network traffic, generally in a firewall implemented in a dedicated machine, running at the gateway between the local network and other networks. DKI Jakarta gets the 2021 APBD budget of Rp. 79.89 trillion rupiah was then allocated for tender needs of 3.87 trillion so that the tender for DKI Jakarta amounted to 519, for IT tender needs it was allocated 743.543 billion with a total tender of 130. Making a decision support system is one way to determine the selection of the best firewall tender. The method used in the decision support system is TOPSIS(Technique For Order Preference by Similarity to Ideal Solution ) because it is able to complete the best and most practical decision making. Based on this description, the research identifies the problem of how effective it is in the use of TOPSIS, assessed not only based on the advantages but also based on the shortcomings for making firewall tender decisions in DKI Jakarta. firewall tenders taken include the procurement of hardware firewalls, web applications, VPN extensions, PPATK firewalls, and Colo VPN extensions. Based on calculations using the TOPSIS method, the highest score value is 0.575657361 with rank 1 so that the best firewall tender is the firewall tender 3. The results of the analysis using the TOPSIS method, it can be concluded that tender 3 is the highest tender value, namely 0.57565 and gets a rank 1 of 4 firewall tenders.